Exploring the beliefs of caregivers about the caregiving experiences of children with acute lymphoblastic leukemia in Malaysia - Agnes Shu Sze Chong; Ahmad Mahadir; Alias Hamidah; Iqbal Hussain Rizuana; Lateh Afifi; Caryn Mei Hsien Chan (Belitung Raya Foundation, Indonesia, 2022)
Background: Cancer is one of the major leading causes of childhood death, and the most common type is acute lymphoblastic leukemia. The survival rate has increased in recent years; however, the long patient trajectory may trigger psychological distress among caregivers as they play an active role in ensuring that the child’s basic needs are met. Being in a patient-focused system, the needs of caregivers may be neglected. Objective: This study aimed to explore the caregivers' beliefs on children with acute lymphoblastic leukemia caregiving experiences in order to promote their well-being. Methods: Caregivers from thirteen families of children with acute lymphoblastic leukemia participated in this phenomenological study. NVivo 12 was used for the thematic analysis of the data. Consolidated criteria for reporting qualitative research (COREQ) were used in this study. Results: Overall, five main themes for caregivers’ beliefs were identified from their responses: 1) dietary intake with emphasis on its importance in aiding recovery and its potential influence on cancer complications, 2) childcare which emphasized the need to be strong and self-sacrifice, 3) treatment which reflected the use of home or natural remedies and caregivers’ negative perception towards chemotherapy, 4) causes of cancer believed to be linked to early childcare choices on food, beverage, and stress imposed on the child, and 5) source of beliefs that included doctors, online platforms, personal encounters and information on food labels. Conclusion: Caregivers’ beliefs are varied and nuanced, formed in a multicultural social background of Malaysia. These findings provide knowledge for future supportive cancer care for patients, their caregivers, and the treatment outcome in the Malaysian context. Nurses, who play an essential role between healthcare professionals and patients and/or their caregivers, can be empowered to provide psychological support, early detection of psychological distress, and exploration of caregiver beliefs, given that the number of clinical psychologists in Malaysia is lacking, and there is greater preference for care to be provided by doctors or nurses.